High cholesterol and low triglycerides are associated with total lumbar bone mineral density among adults aged 50 years and over: The NHANES 2017–2020 - Wang, Peng; Chen, Cong; Song, Chunhao; Jia, Jun; Wang, Yuanhao; Mu, Weidong (Frontiers in Medicine, 2022)
Background: The association between cholesterol and triglycerides with the lumbar bone mineral density (BMD) was widely investigated, but the results remained conflicting. This study aimed to investigate the relationship between total cholesterol, triglycerides and total lumbar BMD in adults. Methods: This cross-sectional study included 1985 individuals aged 50 years and over. The data on total cholesterol, triglycerides, total lumbar BMD and other covariates were obtained from the National Health and Nutritional (NHANES) between 2017 and March 2020 pre-pandemic. Multivariate logistic regression models were utilized to investigate the association between cholesterol, triglycerides and total lumbar BMD. Smooth curve fittings and generalized additive models were also used to analyze the potential nonlinearity. Results: 901 males and 1084 females with a mean age of 63.02± 8.72 years (age 50 to 80 years) were included in this study. In multivariate regression analysis, the association between cholesterol and total lumbar BMD was negative (β=-0.026, 95% CI: -0.033, -0.020). This relationship still existed after adjusted for gender and race (β=-0.018, 95% CI: -0.025, -0.012) and fully adjusted for all covariates (β=-0.022, 95% CI: -0.029, -0.015). The association between triglycerides and total lumbar BMD was positive (β=0.024, 95% CI: 0.017, 0.031). This relationship still existed after adjusted for gender and race (β=0.021, 95% CI: 0.015, 0.028) and fully adjusted for all covariates (β=0.021, 95% CI: 0.014, 0.028). In threshold effect analysis, the relationship between triglycerides and total lumbar BMD was an inverted U-shaped curve with the inflection point at 2.597 mmol/L. Conclusion: High levels of total cholesterol and relative low levels of triglycerides are significantly associated with total lumbar BMD in adults aged 50 years and over.